2003
DOI: 10.1016/s1097-2765(03)00186-2
|View full text |Cite
|
Sign up to set email alerts
|

Histones Are First Hyperacetylated and Then Lose Contact with the Activated PHO5 Promoter

Abstract: We have analyzed the histone modification status of the PHO5 promoter from yeast by the ChIP technology and have focused on changes occurring upon activation. Using various acetylation-specific antibodies, we found a dramatic loss of the acetylation signal upon induction of the promoter. This turned out to be due, however, to the progressive loss of histones altogether. The fully remodeled promoter appears to be devoid of histones as judged by ChIP analyses. Local histone hyperacetylation does indeed occur, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
303
3
13

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(358 citation statements)
references
References 43 publications
39
303
3
13
Order By: Relevance
“…Recruitment is mediated either by activator proteins bound at promoter regions (17)(18)(19)(20)(21) or by elongating Pol II (and associated factors) at highly transcribed genes (21-24). We presume that the nucleosome-remodeling complexes and/or histone chaperones responsible for rapid histone exchange differ from those used during DNA replication.…”
Section: Relative Ip Efficiencymentioning
confidence: 99%
“…Recruitment is mediated either by activator proteins bound at promoter regions (17)(18)(19)(20)(21) or by elongating Pol II (and associated factors) at highly transcribed genes (21-24). We presume that the nucleosome-remodeling complexes and/or histone chaperones responsible for rapid histone exchange differ from those used during DNA replication.…”
Section: Relative Ip Efficiencymentioning
confidence: 99%
“…1): (i) sliding, or moving the histone octamer to a new position, which exposes DNA 10-12 ; (ii) ejection, or completely displacing the octamer to expose DNA [13][14][15][16] ; (iii) removal of H2A-H2B dimers, leaving only the central H3-H4 tetramer, which exposes DNA and destabilizes the nucleosome 17,18 ; and (iv) dimer replacement-for example, exchanging the resident H2A-H2B dimers for dimers NIH Public Access…”
Section: Remodelers Slide Eject and Restructure Nucleosomesmentioning
confidence: 99%
“…Studies of the yeast PHO5 gene suggest that nucleosomes are removed from the promoter upon activation 15,16 . Interestingly, genomewide analyses show that promoters are intrinsically nucleosome deficient and become more deficient during activation 73,74 .…”
Section: Nucleosome Ejection: Pulling the Rug From Under Your Neighbor?mentioning
confidence: 99%
“…Second, it has been shown that transcriptionally active chromatin is depleted in (H2A-H2B) dimers (11); and this has later been confirmed for RNA polymerase II in vitro (12). Third, recent results indicate that chromatin remodeling at the promoter of the Pho5 gene involves the complete transient loss of histones (13).…”
mentioning
confidence: 91%